Men and Women Defending Themselves from Political Scandals: Gender Stereotypes and Proneness to Forgive Scandalous Politicians. Issue 1 (2nd August 2021) - Cucchi, Silvia; Graziani, Anna Rita; Guidetti, Margherita; Cavazza, Nicoletta
Many studies have highlighted the role of gender stereotypes in impressions of politicians. In general, a politician's image benefits from behaving consistently within gender stereotypes. The present study tested whether this also applied to different image restoration tactics employed by male versus female politicians after a scandal. We assessed participants' evaluation of a fictitious male or female politician soon after a scandal and then after his or her defence. We used a 3 × 2 experimental design to compare the effectiveness of three defensive tactics involving different degrees of assertiveness vs. submissiveness as a function of a politician's gender. All tactics were overall effective in improving the damaged reputation of the fictitious politician but, as expected, using the excuse of mitigating circumstances (submissive) was more beneficial to female politicians while diffusing responsibility by accusing another person (assertive) was more beneficial to male politicians, both in terms of global attitude and stereotypical evaluations (communality and agency, respectively). The tactic of mortification and requests for forgiveness did not have different effects by gender. Theoretical and practical implications are discussed.